Anaesthesia for Living Related Liver Transplantation - Li-Ming Teo MBBS, MMed (Anaesthesiology) (Proceedings of Singapore Healthcare, 2012)
With the greater success of liver transplantation, livers from deceased donors are insufficient to meet the need for livers required for transplantation. In various parts of Asia, living related liver transplantation is the treatment for patients with end-stage liver disease. An overview of anaesthesia for both the donor and the recipient is described. Controversies involving epidural anaesthesia, blood loss prevention and blood conservation techniques in the donor are discussed. Various aspects in the anaesthetic management of the recipient are also looked at.